Hubungan Konflik Peran Ganda dengan Keharmonisan Keluarga pada Wanita Karir di Kota Makassar - Siti Rahmayani Mangnguluang; Faradillah Firdaus; Perdana Kusuma (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
A harmonious family is the dream and hope of every individual. However, not every individual is able to make it happen. Some individuals, including career women, often find it difficult to divide their time between office work and household work, which can lead to conflicts known as dual role conflicts. If this conflict cannot be resolved properly, it will affect family harmony. This research aims to determine the relationship between dual role conflict and family harmony among career women in Makassar City. The subjects in this research were 206 career women subjects who were married, had at least 1 child, worked as private employees and lived in Makassar City. The sampling technique uses accidental sampling. The measuring instruments used in this research are a modified family harmony scale and a modified dual role conflict scale. The results of simple linear regression showed r = -0.462, p = 0.000 (p < 0.05). This coefficient value shows that there is a significant negative relationship between dual role conflict and family harmony. This means that the higher the dual role conflict, the lower the family harmony, and vice versa. The implication of this research is that it is a reference source that can contribute in the form of knowledge regarding dual role conflict and family harmony.